SELF-PERCEPTION OF HEALTH OF ELDERLY RESIDENTS IN A LONG-TERM CARE FACILITY IN THE MUNICIPALITY OF RIO VERDE - GO (CIPEEX, 2023)
The early assessment of self-perceived health of the population in a long-term care institution for the elderly (ILPI) can be important in the overall observation of elderly health as well as in predicting the decline in functionality and even mortality. This study aims to verify the self-perception of health in institutionalized elderly individuals in the municipality of Rio Verde - Goiás. This is a cross-sectional analysis with a quantitative approach, in which institutionalized elderly individuals were investigated regarding their sociodemographic and economic aspects, general health, institutionalization, and self-perception of health. The study population consisted of all elderly residents in the ILPI during the data collection period, including those over 60 years old and excluding those who did not agree to participate in the study. Self-perception of health was assessed by the response to the question: "In general, how would you describe your health?" The response options were: "excellent," "good," "fair," "poor," or "very poor." It was found that the majority of the analyzed elderly have a self-perception classified as very good regarding their health (n=32; 42.7%).
Keywords: Self-perception of health; Long-Term Care Facility for the Elderly; Health of institutionalized elderly